PENYELESAIAN PEMBIAYAAN BERMASALAH AKAD MURABAHAH PERSPEKTIF HUKUM EKONOMI SYARIAH - Fiyo Safira (Al Itmamiy Jurnal Hukum Ekonomi Syariah (Muamalah), 2024)
Murabaha contract financing is a financing product that is quite attractive to customers because besides being easy, the process is also easy. However, even though it is easy and easy murabaha financing also has many problems. There are many factors that experience problematic financing, one of which is that the customer is bankrupt, the economy is declining, the capital does not return. So in this case the BMT must resolve problematic financing according to Islamic law. So the focus of research in this study is how is the practice of murabahah contract financing from the perspective of Sharia Economic Law at BMT NU Grujugan Branch, Bondowoso Regency? and how is the settlement of murabahah contract problem financing from the perspective of Sharia Economic Law at BMT NU Grujugan Branch, Bondowoso Regency?. The research method used in this research is a descriptive method with a qualitative approach with the type of field research (field reseach), the location of this research is located at BMT NU Grujugan Branch, Bondowoso Regency. The data sources used in this research are primary data and secondary data. Data obtained through interviews, observation and documentation. Then when the data has been collected then analyzed using descriptive analysis method. The results of this study indicate that the practice of murabahah contract financing at BMT NU Grujugan Branch, Bondowoso, seen from the pillars and conditions of the murabahah contract financing practice is in accordance with Islamic law. In terms of Sharia Economic Law, the settlement of murabahah contract financing can be said to be appropriate because in the practice of settlement using as-shulhu (peace) then routine billing, giving warnings, rescheduling in the DSN MUI fatwa NO.48/DSN-MUI/II/2005 is also explained, namely "Rescheduling Murabahah Bills" customers are given relief by the BMT and the final step is the sale of collateral.